Garbage Practices and Consumption ¿A Habitus? - Cirett Galan, Diana Blanca (2025)
The relentless generation of urban solid waste, driven by the population growth of the last century and current consumption-disposal practices, represents a global municipal challenge due to its harmful effects. Its consequences impact various dimensions: health, public space, the environment, and society, among others. A comprehensive study was conducted in Guaymas and San Carlos, Sonora, Mexico, from 2019 to 2022, with the general objective of understanding how the meanings and practices around waste are shaped by gender identity, social class, sense of belonging, and public management in both public and private spaces. This article focuses on how consumerism affects the everyday waste-related practices of men and women in public spaces. The methodology was qualitative and descriptive, using the ethnographic method over five and a half months, with techniques such as observation, casual conversation, and semi-structured interviews conducted with ten informants and four key subjects related to urban solid waste. The findings revealed gender, social class, and belonging-related components connected to waste practices, as well as a differentiation of habitus between the two populations. In one group, there is a tendency to dispose of waste in public spaces, driven by habitual consumerism. This interaction is shaped by cultural, attitudinal, and public management factors—the latter influenced by the lack of policies that encourage individuals to adopt more responsible waste practices.